CATALYTIC CONVERSION OF ALGAE TO BIOFUEL USING METAL SUPPORTED ON ZEOLITE - Mardhiahtul Iftiah Ariffin (Tesis, 2018)
The main objectives of this research is to study the catalytic activity of metal oxide catalysts for transesterification reaction of micoralgae oil to biodiesel.